Urinary F(2)-Isoprostanes as a Biomarker of Reduced Risk of Type 2 Diabetes - Il'yasova, Dora (American Diabetes Association, 2012)
OBJECTIVE: We have previously reported evidence of an inverse association between a urinary F(2)-isoprostane and type 2 diabetes risk in a pilot case-control study nested within the Insulin Resistance Atherosclerosis Study (IRAS). Here, we report the results from the study extended to the entire IRAS cohort. RESEARCH DESIGN AND METHODS: This prospective study included 138 incident type 2 diabetes case and 714 noncase subjects. Four F(2)-isoprostanes (iPF2α-III; 2,3-dinor-iPF2α-III; iPF2α-VI; and 8,12-iso-iPF2α-VI) were assayed in baseline urine samples using liquid chromatography–tandem mass spectrometry. RESULTS: Three F(2)-isoprostanes showed significant inverse associations with type 2 diabetes risk: the adjusted odds ratios were 0.52 (95% CI 0.39–0.67), 0.56 (0.42–0.73), 0.62 (0.48–0.79), and 0.91 (0.72–1.12) for iPF2α-III; 2,3-dinor-iPF2α-III; iPF2α-VI; and 8,12-iso-iPF2α-VI, respectively. CONCLUSIONS: Our findings indicate that urinary F(2)-isoprostanes are inversely associated with type 2 diabetes risk beyond the traditional risk factors and may be useful in identifying high-risk populations.